Wallace Stegner and the Western Environment: Hydraulics, Placelessness, and (Lack of) Identity - Fredrik Chr. Brøgger (European Journal of American Studies, 2011)
This article is chiefly concerned with Wallace Stegner’s ideas of aridity as the key to the understanding of the history and culture of the American West. It first examines the arguments of some major books published in the 1980s that helped strengthen Stegner’s conviction that the West was heading towards environmental disaster due to the rapidly increasing depletion of its rivers and aquifers, a projected ecological crisis that has grown even more acute at the beginning of the 21st century. The subsequent focus of this article, however, is on Stegner’s predominant proposition that the abuse of the arid nature of the West – the rampant disregard of its environmental limitations – is a product of a mindset and a culture that he finds particularly Western. In the course of his analysis, Stegner sees the rootlessness that typified his own family history as a direct reflection of the transientness characteristic of the collective history of the American West, which served to hamper the evolution of a sense of place that in his view is the prerequisite for a genuine stewardship of the land.